(untitled) (Letras, 2019)
There is a consensus in considering Sendebar or Libro de los engaños y asayamientos de las mujeres —a book whose translation from the Arabic was commissioned by the prince don Fadrique in 1253— as an exponent of late medieval misogynous thinking, especially because it contains a large amount of stories that illustrate the deeds of adulterous, deceitful and treacherous women. Within this group of tales, we find two exempla whose protagonists are two old alcahuetas, old ladies who induce faithful women into adultery, using different kinds of tricks: Canicula and Pallium, narrated by the fitfth and the sixth advisers respectively. Bearing in mind that these tales have antecedents in oriental collections such as One Thousand and One Nights and One Hundred and One Nights, we will develop an analysis of the figure of the old procuress and her actions within each tale, taking into account, in particular, the character’s resignification as a consequence of the intercultural passage. The comparison with the oriental versions will clarify the particularities of the Hispanic text, especially with regard to its alleged misogynist tone and its insertion within the exemplary genre.